(8x+7)(8x+7)(4x+3)(x+1)=15

Simple and best practice solution for (8x+7)(8x+7)(4x+3)(x+1)=15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8x+7)(8x+7)(4x+3)(x+1)=15 equation:


Simplifying
(8x + 7)(8x + 7)(4x + 3)(x + 1) = 15

Reorder the terms:
(7 + 8x)(8x + 7)(4x + 3)(x + 1) = 15

Reorder the terms:
(7 + 8x)(7 + 8x)(4x + 3)(x + 1) = 15

Reorder the terms:
(7 + 8x)(7 + 8x)(3 + 4x)(x + 1) = 15

Reorder the terms:
(7 + 8x)(7 + 8x)(3 + 4x)(1 + x) = 15

Multiply (7 + 8x) * (7 + 8x)
(7(7 + 8x) + 8x * (7 + 8x))(3 + 4x)(1 + x) = 15
((7 * 7 + 8x * 7) + 8x * (7 + 8x))(3 + 4x)(1 + x) = 15
((49 + 56x) + 8x * (7 + 8x))(3 + 4x)(1 + x) = 15
(49 + 56x + (7 * 8x + 8x * 8x))(3 + 4x)(1 + x) = 15
(49 + 56x + (56x + 64x2))(3 + 4x)(1 + x) = 15

Combine like terms: 56x + 56x = 112x
(49 + 112x + 64x2)(3 + 4x)(1 + x) = 15

Multiply (49 + 112x + 64x2) * (3 + 4x)
(49(3 + 4x) + 112x * (3 + 4x) + 64x2 * (3 + 4x))(1 + x) = 15
((3 * 49 + 4x * 49) + 112x * (3 + 4x) + 64x2 * (3 + 4x))(1 + x) = 15
((147 + 196x) + 112x * (3 + 4x) + 64x2 * (3 + 4x))(1 + x) = 15
(147 + 196x + (3 * 112x + 4x * 112x) + 64x2 * (3 + 4x))(1 + x) = 15
(147 + 196x + (336x + 448x2) + 64x2 * (3 + 4x))(1 + x) = 15
(147 + 196x + 336x + 448x2 + (3 * 64x2 + 4x * 64x2))(1 + x) = 15
(147 + 196x + 336x + 448x2 + (192x2 + 256x3))(1 + x) = 15

Combine like terms: 196x + 336x = 532x
(147 + 532x + 448x2 + 192x2 + 256x3)(1 + x) = 15

Combine like terms: 448x2 + 192x2 = 640x2
(147 + 532x + 640x2 + 256x3)(1 + x) = 15

Multiply (147 + 532x + 640x2 + 256x3) * (1 + x)
(147(1 + x) + 532x * (1 + x) + 640x2 * (1 + x) + 256x3 * (1 + x)) = 15
((1 * 147 + x * 147) + 532x * (1 + x) + 640x2 * (1 + x) + 256x3 * (1 + x)) = 15
((147 + 147x) + 532x * (1 + x) + 640x2 * (1 + x) + 256x3 * (1 + x)) = 15
(147 + 147x + (1 * 532x + x * 532x) + 640x2 * (1 + x) + 256x3 * (1 + x)) = 15
(147 + 147x + (532x + 532x2) + 640x2 * (1 + x) + 256x3 * (1 + x)) = 15
(147 + 147x + 532x + 532x2 + (1 * 640x2 + x * 640x2) + 256x3 * (1 + x)) = 15
(147 + 147x + 532x + 532x2 + (640x2 + 640x3) + 256x3 * (1 + x)) = 15
(147 + 147x + 532x + 532x2 + 640x2 + 640x3 + (1 * 256x3 + x * 256x3)) = 15
(147 + 147x + 532x + 532x2 + 640x2 + 640x3 + (256x3 + 256x4)) = 15

Combine like terms: 147x + 532x = 679x
(147 + 679x + 532x2 + 640x2 + 640x3 + 256x3 + 256x4) = 15

Combine like terms: 532x2 + 640x2 = 1172x2
(147 + 679x + 1172x2 + 640x3 + 256x3 + 256x4) = 15

Combine like terms: 640x3 + 256x3 = 896x3
(147 + 679x + 1172x2 + 896x3 + 256x4) = 15

Solving
147 + 679x + 1172x2 + 896x3 + 256x4 = 15

Solving for variable 'x'.

Reorder the terms:
147 + -15 + 679x + 1172x2 + 896x3 + 256x4 = 15 + -15

Combine like terms: 147 + -15 = 132
132 + 679x + 1172x2 + 896x3 + 256x4 = 15 + -15

Combine like terms: 15 + -15 = 0
132 + 679x + 1172x2 + 896x3 + 256x4 = 0

The solution to this equation could not be determined.

See similar equations:

| 3(15x)+7y=208 | | -X-17=3x-1 | | 0.5(6k-0.5)-0.5(3k-0.25)-0.8(5k-2)=0 | | 3(15x)+7x=208 | | -3x-5x-1=0 | | (5ab)(-1/3a)(9b^2) | | Ln(x+2)+5=7 | | sin(6)-sin(42)-sin(66)+sin(78)=-0.5 | | sin(6)-sin(42)-sin(66)+sin(78)=0 | | 0.16=W/5 | | y=4x^3-3x^2+x^6 | | cos(5x)+cos(3x)=cos(x) | | 3logX=9 | | 5-5n=10 | | 6*5/9 | | I=w/V | | 7(4)-7=21 | | I=0.8/5 | | (10x-14)=(5x+56) | | 14(-8x-15)=-1218 | | 10x^2-25x/12=5 | | 0.20=W/5 | | 2x/3-7=2 | | 2x(6-2)=16 | | -4x(3x-5y^2+2)= | | x+21=147 | | 3x^2=-x-3 | | 8y+4=16y-17 | | 30+100+x-1=180 | | 2x^2=5+x | | 115+40+3x+1=180 | | 40+35+x-5=180 |

Equations solver categories